2017
DOI: 10.1039/c7ta01106g
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of an eco-friendly nitrogen–phosphorus ammonium salt to enhance the durability and flame retardancy of cotton

Abstract: An eco-friendly AEGDP flame retardant reacted with –OH groups from cotton to enhance the durability and flame retardancy of cotton fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…As shown in Figure 6 a,b, both Cotton-PDTSP-1T and Cotton-PDTSP-2T began to degrade at 279 °C ( T 5% , the temperature at 5 wt % weight loss) and the maximum rate degradation temperature ( T max ) appeared at 319 °C. These temperatures were lower than control fabrics and might be due to the dehydration of cellulose catalyzed by phosphorus/polyphosphoric acid generated from PDTSP during thermal degradation [ 31 , 32 ]. However, over 60% and 30% of char residue at T max and 800 °C could remain for Cotton-PDTSP-1T and Cotton-PDTSP-2T, and they were much higher than control cotton (43% and 11%), which indicated that PDTSP could greatly improve the thermal stability and char-forming properties of cotton fabrics.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 6 a,b, both Cotton-PDTSP-1T and Cotton-PDTSP-2T began to degrade at 279 °C ( T 5% , the temperature at 5 wt % weight loss) and the maximum rate degradation temperature ( T max ) appeared at 319 °C. These temperatures were lower than control fabrics and might be due to the dehydration of cellulose catalyzed by phosphorus/polyphosphoric acid generated from PDTSP during thermal degradation [ 31 , 32 ]. However, over 60% and 30% of char residue at T max and 800 °C could remain for Cotton-PDTSP-1T and Cotton-PDTSP-2T, and they were much higher than control cotton (43% and 11%), which indicated that PDTSP could greatly improve the thermal stability and char-forming properties of cotton fabrics.…”
Section: Resultsmentioning
confidence: 99%
“…There are two widely used and representative industrialized phosphorous‐containing flame retardants namely Pyrovatex and Proban, both of them have excellent flame retardancy and durability . But they will release formaldehyde and corrosive hydrogen halide gas if for long‐term use, which unable to meet the requirements of modern environmental safety, so that restrict their application.…”
Section: Introductionmentioning
confidence: 99%
“…A component of white vinegar, 3–7 wt % acetic acid, is responsible for the enhanced degradation of CFs. The acid is regarded as a catalyst to promote the dehydration of cellulose . We used an aqueous solution containing acetic acid (3 wt %) instead of white vinegar as the invisible ink, to investigate whether acetic acid could trigger the color change (experimental results are shown in Figure S14 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The acid is regarded asacatalyst to promote the dehydration of cellulose. [33,34] We used an aqueous solution containing acetic acid (3 wt %) insteado fw hite vinegara st he invisible ink, to investigate whether acetic acid could trigger the color change (experimentalr esults are shown in Figure S14 in the Supporting Information). The acetic acid treated CF/HAPNW paper exhibited the same color-changing behavior with an aqueous solution of acetic acid as that with white vinegari nr esponse to fire.…”
Section: Abbreviationmentioning
confidence: 99%